Manufacturing method for zeolite heavy metal stabilizer based on bottom ash doped with iron oxide particles, and stabilizing method for heavy metal contaminated sediment using the same
Patent Information
- Application Number
- KR1020240158515
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2026-10-21
- Estimated Expiration
- 2044-11-08
Smart Images

Figure 112024123184751-PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a bottom material-based zeolite heavy metal stabilizer supported with iron oxide particles and a method for stabilizing heavy metal contaminated sediments using the same. Background Technology
[0002] This achievement was made possible through the support of the Ansan Green Environment Support Center for the "Development of Coal Bottom Ash-Based Stabilization Materials for Reducing Risks of Heavy Metal-Contaminated Dredged Sediments (Project No.: 24-07-04-60-61)".
[0003] As science, technology, and industry develop today, the demand for electrical energy continues to increase, and consequently, the operating volume of coal-fired power plants is also continuously rising. Consequently, the generation of coal ash (or coal ash) as a byproduct of combustion from coal-fired power plants is increasing rapidly. Meanwhile, according to a 2014 report by the Korea Environment Institute, more than 8 million tons of coal ash are discharged annually from domestic thermal power plants. Of this, while the recycling rate for fly ash is 75 to 80%, the recycling rate for bottom ash is very low, and most of it is disposed of by landfilling at ash disposal sites.
[0004] Meanwhile, coal ash is also known as a suitable precursor material for zeolite synthesis because it contains large amounts of silicon (Si) and aluminum (Al). Zeolites are three-dimensional tetrahedral aluminosilicate minerals containing Al 3+ Si by 4+ The negative charge generated by the homomorphic substitution of and the cation (Na) to balance it. + , Ca 2+ , Mg 2+Zeolites are materials that possess ions and water molecules in their pores and channels. Meanwhile, while naturally occurring zeolites have pores and channels of limited size, coal ash-based zeolites possess diverse pore structures and are known as air and water purification materials with significant potential for economic utilization. Furthermore, zeolites are porous inorganic compounds used as catalysts and catalyst supports; they are materials capable of having various structures through synthesis and are widely used in the treatment of wastewater and waste containing heavy metals and radioactive materials due to their excellent cation exchange properties. However, although zeolites exhibit excellent reactivity toward divalent heavy metal cations due to their superior cation exchange capacity, their reactivity toward trivalent or pentavalent arsenic existing as oxyanions in sediments is low; therefore, research on surface modification is necessary to simultaneously stabilize arsenic and heavy metals.
[0005] Meanwhile, sediment refers to a mixture of various substances that has settled at the bottom of a body of water. It includes byproducts of benthic organisms (shells and carcasses), eroded soil particles flowing in from the surface, organic matter (plant bodies and animal carcasses, etc.), sewage, industrial waste, other organic and inorganic substances, and chemical substances. Depending on the purpose of dredging, sediment is classified as sludge for pollution removal and separated as waste. On the other hand, according to reports from the Marine Environment Research Institute, high concentrations of heavy metal contamination exceeding standard limits have been found in sediments collected from rivers near industrial complexes. These contaminated sediments continuously pollute water systems and negatively impact surrounding ecosystems by repeatedly adsorbing and desorbing pollutants depending on the environment. In particular, while sediments within the soil contamination concern standards can be utilized as resources such as embankment material, sediments contaminated with high concentrations are difficult to utilize as resources. Furthermore, due to the nature of the contamination, treatment is difficult and inefficient; consequently, such dredged sediments are currently mainly disposed of through landfill.
[0006] Accordingly, the Ministry of Environment adopted and applied the stabilization method as an alternative risk reduction measure for the first time in Korea for the soil contamination remediation project around the Janghang Smelter. Stabilization technology is a technique that reduces risk by injecting a stabilizer into contaminated soil or waste to chemically convert pollutants into a stabilized form (through precipitation, formation of insoluble compounds, adsorption, etc.), thereby reducing leaching, mobility, and bioavailability.
[0007] In the United States, the USEPA designated stabilization technology as the Best Demonstrated Available Technology (BDAT) as a treatment technology to reduce the risks of dozens of types of hazardous waste specified in the Resource Conservation and Recovery Act (RCRA) of 1993, and since then, much research has been conducted on the development of various stabilizers. The problem to be solved
[0008] Against this background, the present invention aims to provide a bottom ash-based zeolite heavy metal stabilizer loaded with iron oxide particles and a method for stabilizing heavy metal contaminated sediment using the same, which can simultaneously stabilize heavy metals such as cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), or nickel (Ni) and anionic heavy metals such as arsenic present in contaminated sediment by manufacturing Na-A zeolite from bottom ash generated in a thermal power plant, loading iron ions through an ion exchange reaction, and then manufacturing it into a bead form.
[0009] Furthermore, the technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned technical problems will be clearly understood by those skilled in the art to which the present invention belongs from the description below. means of solving the problem
[0010] The present specification provides a method for manufacturing a heavy metal stabilizer, comprising: a) a step of manufacturing Na-A zeolite from bottom ash; b) a step of preparing Fe-A zeolite by supporting iron ions on the Na-A zeolite; and c) a step of manufacturing Fe-A zeolite beads by mixing an inorganic binder and water with the Fe-A zeolite and calcining it.
[0011] For example, the above step a may include the step (a-1) of washing and drying the dried flooring with distilled water and a 0.1 M nitric acid solution.
[0012] For example, step a may include a step (a-2) of mixing dried flooring material with sodium hydroxide (NaOH) in a weight ratio of 1:1 to 2 parts and melting the mixture in a temperature range of 500 to 600 ℃ to extract silicon (Si) and aluminum (Al) from the flooring material.
[0013] For example, step a may include a step (a-3) of mixing the molten product with water to produce an aluminosilicate gel and mixing sodium aluminate (NaAlO2) to adjust the molar ratio of silicon (Si) and aluminum (Al).
[0014] For example, the above step a may include a step (a-4) of forming a Na-A zeolite by hydrothermally reacting the aluminosilicate gel at a temperature range of 90 to 110 ℃ for 4 to 8 hours.
[0015] For example, step b above contains 0.01 to 0.1 M of trivalent iron (Fe) based on 1 part by weight of Na-A zeolite. 3+ ) Mix 10 to 100 parts by weight of the solution and stir for 1 to 48 hours at a temperature in the range of 70 to 90 ℃, so that Na in the Na-A zeolite + Ions and Fe in trivalent iron solution 3+It may include a step (b-1) of inducing ion exchange between ions.
[0016] For example, the above step b may include the step (b-2) of filtering and washing the mixture after the ion exchange is completed, and drying it at a temperature in the range of 100 to 110 ℃ for 1 to 4 hours.
[0017] For example, the above step c may include the step (c-1) of preparing a mixture of Fe-A zeolite, bentonite, and water into beads and drying at a temperature in the range of 100 to 140 ℃ for 1 to 3 hours.
[0018] For example, the above step c may include the step (c-2) of producing flooring-based Fe-A zeolite beads by calcining the dried beads at a temperature in the range of 600 to 700 ℃ for 1 to 10 hours.
[0019] In addition, the present specification provides a heavy metal stabilizer having a bead shape as a bottom-material-based zeolite supported with iron oxide (γ-Fe2O3) and manufactured by the above method.
[0020] For example, the stabilizer has a diameter in the range of 1 to 5 mm, and a BET specific surface area of 50 to 200 m² 2 / g can be.
[0021] For example, the above stabilizer may have a stabilization efficiency of 1 to 99% for arsenic (As) contained in the dredged soil sediment, based on the TCLP (toxicity characteristics leaching product) leaching test results depending on the particle size, concentration, and application ratio of the sediment.
[0022] For example, the above stabilizer may have a stabilization performance of 1 to 99% for heavy metals such as cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), or nickel (Ni) contained in the dredged soil sediment, based on the TCLP (toxicity characteristics leaching product) leaching test results depending on the particle size, concentration, and application ratio of the sediment.
[0023] In addition, the present specification provides a method for stabilizing heavy metal contaminated sediment, comprising the steps of: adding and mixing the heavy metal stabilizer to the arsenic and cationic heavy metal contaminated sediment; and adjusting the moisture content of the arsenic and cationic heavy metal contaminated sediment to 10 to 30%.
[0024] For example, when adding the above stabilizer, 1 to 10 parts by weight of the heavy metal stabilizer can be added based on 100 parts by weight of sediment contaminated with arsenic and cationic heavy metals. Effects of the invention
[0025] The flooring-based zeolite heavy metal stabilizer according to the present invention can simultaneously stabilize complex contaminated sediments caused by arsenic and cationic heavy metals by improving the characteristics of zeolite, which has excellent reactivity toward cationic heavy metals but low reactivity toward pollutants existing as oxyacid anions such as trivalent arsenic and pentavalent arsenic.
[0026] In addition, by manufacturing heavy metal stabilizers in the form of beads, unlike conventional powder materials, there is no risk of loss, and it is possible to prevent contamination of the surrounding ecosystem and groundwater caused by toxic substances leaching from sediments after marine or landfilling of contaminated sediments.
[0027] Furthermore, the zeolite heavy metal stabilizer of the present invention is made by recycling bottom materials that were conventionally landfilled as industrial waste, and thus has excellent effects in terms of securing economic viability through resource recycling and preventing environmental pollution. Brief explanation of the drawing
[0028] FIG. 1 illustrates a method for stabilizing heavy metal contaminated sediment using a heavy metal stabilizer according to an embodiment of the present invention. FIG. 2 illustrates a method for manufacturing a flooring-based Na-A zeolite according to an embodiment of the present invention, and FIG. 3 shows the XRD analysis results of the Na-A zeolite. FIG. 4 illustrates a method for manufacturing a flooring-based Fe-A zeolite according to an embodiment of the present invention, and FIG. 5 illustrates Na during the manufacturing of the Fe-A zeolite + Ions and Fe 3+ This represents the mechanism of ion exchange between ions. FIG. 6 illustrates a method for manufacturing flooring-based zeolite heavy metal stabilizer beads according to an embodiment of the present invention, and FIG. 7 is the XRD analysis result of the heavy metal stabilizer beads. Figure 8 is a photograph of a heavy metal stabilizer bead according to an embodiment of the present invention. FIG. 9 is a photograph of a contaminated sediment and a photograph of the collection site taken to confirm the purification effect of the heavy metal stabilizer beads according to one embodiment of the present invention on the contaminated sediment, and the collection site is the downstream of Singilcheon, a stream passing through the Sihwa-Banwol Industrial Complex. FIG. 10 shows the heavy metal content in contaminated sediment collected to confirm the purification effect of the heavy metal stabilizer beads according to one embodiment of the present invention on contaminated sediment. FIG. 11 illustrates the stabilization treatment process for contaminated sediment using heavy metal stabilizer beads according to one embodiment of the present invention. Figure 12 shows the results of a TCLP test conducted before and after stabilization treatment of contaminated sediment with heavy metal stabilizer beads according to an embodiment of the present invention. FIG. 13 is an expected mechanism related to the stabilization of contaminated sediments by heavy metal stabilizer beads according to one embodiment of the present invention. Specific details for implementing the invention
[0029] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings. However, in describing this description, descriptions of already known functions or configurations will be omitted to clarify the gist of this description.
[0030] The term "bottom ash," used throughout the specification and claims of the present invention, should be understood to mean the ash remaining after excluding fly ash from coal ash generated in an incinerator, and which exists on the bottom of an ash disposal site such as a thermal power plant.
[0032] As described above, according to the prior art, zeolites widely used as heavy metal stabilizers have excellent reactivity with cationic heavy metals such as lead, copper, and cadmium, but lack reactivity with oxyanions such as trivalent arsenic or pentavalent arsenic, so in order to simultaneously stabilize cationic heavy metals and trivalent arsenic or pentavalent arsenic anions present in contaminated soil or sediment, a separate surface modification had to be performed on the surface of the zeolite.
[0033] Meanwhile, the inventors produced Na-A zeolite from bottom ash, performed ion exchange on the Na-A zeolite to produce Fe-A zeolite, and then produced it in the form of beads. In this case, it is possible to simultaneously reduce not only cationic heavy metals such as lead, copper, and cadmium present in contaminated sediments, but also oxyacid anions such as trivalent or pentavalent arsenic. Unlike conventional powder-type stabilizers, there is no risk of loss, and since bottom ash that was previously landfilled as industrial waste is recycled, it has excellent advantages in terms of securing economic viability and preventing environmental pollution. Based on these experiments, the present invention was completed.
[0035] Method for manufacturing a flooring-based zeolite heavy metal stabilizer
[0036] Specifically, a method for manufacturing a bottom ash-based heavy metal stabilizer supported with iron oxide particles according to one embodiment of the present invention may include: a) a step of manufacturing Na-A zeolite from bottom ash; b) a step of preparing Fe-A zeolite by supporting iron ions on the Na-A zeolite; and c) a step of manufacturing Fe-A zeolite beads by mixing an inorganic binder and water with the Fe-A zeolite and calcining (see FIG. 1, 2, 4 and 6).
[0038] First, Na-A zeolite is prepared from bottom ash (step a).
[0039] In the present invention, bottom ash is the remaining coal ash (or coal ash) generated through an incineration process at a thermal power plant, excluding fly ash. In one embodiment of the present invention, the bottom ash of step a may be prepared by washing bottom ash collected from a thermal power plant with distilled water and a 0.1 M nitric acid solution for 1 hour and drying it for 1 to 3 hours, specifically 2 hours (step a-1).
[0040] Meanwhile, the dried bottom material and sodium hydroxide (NaOH) are introduced into an ignition device, mixed in a weight ratio of 1:1 to 2 parts, specifically 1:1.5 parts, and heated and melted at a temperature range of 500 to 600 ℃, specifically 550 ℃, to extract silicon (Si) and aluminum (Al) from the bottom material (step a-2). In the above process, by mixing the bottom material with sodium hydroxide in the above weight ratio range and heating and melting it at the above temperature range, there may be an advantage in extracting silicon (Si) and aluminum (Al) in a ratio suitable for forming Na-A zeolite.
[0041] Next, the above molten product is mixed with water to prepare an aluminosilicate gel, and sodium aluminate (NaAlO2) is mixed to adjust the molar ratio of silicon (Si) to aluminum (Al) (step a-3). Specifically, when mixing the molten product with distilled water, it is mixed in a weight ratio of 1:5 to 15, more specifically 1:10, and then a Na-Al zeolite (NaAlO2) with a molar ratio of silicon (Si) to aluminum (Al) of 1:1 is prepared. 12 Al 12 Si 12 O 48· An aluminosilicate gel is prepared by mixing a bottom material and sodium aluminate in a weight ratio of 1:0.1 to 0.5, specifically 1:0.3, to form 27H2O, and stirring for 4 to 8 hours, specifically 6 hours.
[0042] Next, the aluminosilicate gel is placed in a hydrothermal reactor (teflon-lined autoclave) and hydrothermally reacted at a temperature of 90 to 110 °C, specifically 100 °C, for 4 to 8 hours, specifically 6 hours to form a bottom-material-based Na-A zeolite (step a-4).
[0043] Meanwhile, the Na-A zeolite produced through the above reaction may be a synthetic zeolite having an 'LTA' structure consisting of an 8-membered ring (8MR) with a diameter of 0.41 nm and six small windows connected to an α-cage with a diameter of 1.14 nm.
[0045] Next, Fe-A zeolite is prepared by supporting iron ions on Na-A zeolite (step b).
[0046] Step b is the Na in the Na-A zeolite prepared from the flooring material through Step a above. + ions of trivalent iron (Fe 3+ trivalent iron (Fe) in a solution containing ) 3+As a step for ion exchange with ), specifically, 0.01 to 0.1 M of trivalent iron (Fe) based on 1 part by weight of the Na-A zeolite. 3+ ) Mix 10 to 100 parts by weight of the solution and stir for 1 to 48 hours at a temperature in the range of 70 to 90 ℃, so that Na in the Na-A zeolite + Ions and Fe in trivalent iron solution 3+ This can be performed by inducing ion exchange between ions (step b-1).
[0047] Next, the mixture in which the ion exchange is completed is filtered and washed, and dried at a temperature in the range of 100 to 110 ℃ for 1 to 4 hours. Specifically, the washing process may be performed using distilled water until the pH of the washing water reaches 6 to 7 (step b-2).
[0049] Next, Fe-A zeolite is mixed with an inorganic binder and water and calcined to produce Fe-A zeolite beads (step c).
[0050] Step c is performed to resolve the limitations caused by the possibility of loss after application associated with conventional powder-form materials. Specifically, the above step may involve a process of preparing a mixture of Fe-A zeolite, an inorganic binder, and water into beads, and drying it at a temperature in the range of 100 to 140°C for 1 to 3 hours. The inorganic binder used at this time is not limited as long as it enables the production of beads, but bentonite may be used as an example. In addition, the above mixture may be formed by mixing 10 to 20 parts by weight of bentonite and 35 to 40 parts by weight of water when Fe-A zeolite is 40 to 60 parts by weight, and more specifically, when Fe-A zeolite is 46.8 parts by weight, bentonite and 37.5 parts by weight of water may be mixed. In addition, the above mixture may be fed into, for example, an extrusion device for making pills and molded into a bead shape, and may be dried for 1 to 3 hours, specifically 2 hours, under temperature conditions in the range of 100 to 140 ℃ (step c-1).
[0051] Next, the dried beads are calcined at a temperature in the range of 600 to 700 ℃ for 1 to 10 hours to produce flooring-based Fe-A zeolite beads. The calcination can be performed in an ignition furnace, for example, by calcining at a temperature of 650 ℃ for 5 hours (step c-2).
[0053] Iron oxide-supported flooring-based zeolite heavy metal stabilizer
[0054] Meanwhile, the iron oxide-supported flooring-based zeolite stabilizer according to one embodiment of the present invention, which can be manufactured through the steps described above, may be supported with iron oxide (γ-Fe2O3) and may have a bead shape. Specifically, the iron oxide (γ-Fe2O3) may be formed by the following formula 1.
[0056] <Equation 1>
[0058] The above zeolite stabilizer can simultaneously stabilize cation heavy metals such as cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), or nickel (Ni), as well as oxyanions such as trivalent arsenic and pentavalent arsenic, contained in sediments contaminated with heavy metals by pollutants such as wastewater and waste discharged from national industrial complexes, etc., where manufacturing, chemical products, and metal industries are located.
[0059] Specifically, the stabilizer has a diameter in the range of 1 to 5 mm, more specifically in the range of 2 to 3 mm, and a BET specific surface area of 50 to 200 m² 2 It can be / g.
[0060] Meanwhile, the above stabilizer may have a stabilization efficiency of 1 to 99% for arsenic (As) contained in the dredged soil sediment, based on the TCLP (toxicity characteristics leaching product) leaching test results depending on the particle size, concentration, and application ratio of the sediment.
[0061] In addition, the above stabilizer may have a stabilization efficiency of 1 to 99% for heavy metals such as cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), or nickel (Ni) contained in the dredged soil sediment, based on the results of a TCLP (toxicity characteristics leaching product) leaching test depending on the particle size, concentration, and application ratio of the sediment.
[0063] Meanwhile, the above stabilization efficiency can be calculated according to Equation 2 below.
[0065] <Equation 2>
[0067] Method for stabilizing heavy metal contaminated sediments
[0068] Meanwhile, a method for stabilizing heavy metal-contaminated sediment using the heavy metal stabilizer according to the present invention may include the steps of: adding and mixing the heavy metal stabilizer to the sediment contaminated with arsenic and cationic heavy metals; and adjusting the moisture content of the sediment contaminated with arsenic and cationic heavy metals to 10 to 30%. Specifically, when the moisture content is adjusted to 10 to 30% after adding the heavy metal stabilizer, the reaction between the contaminant on the surface of the sediment and the stabilizer can be promoted, thereby enhancing the chemical stabilization effect of the contaminant.
[0069] In addition, when adding the above stabilizer, 1 to 10 parts by weight of the heavy metal stabilizer can be added based on 100 parts by weight of sediment contaminated with arsenic and cationic heavy metals, and within the above weight range, sufficient heavy metal stabilization efficiency and economic feasibility can be secured.
[0071] Meanwhile, the flooring material-based zeolite heavy metal stabilizer according to the present invention, as described above, can simultaneously stabilize complex contaminated sediments caused by arsenic and cationic heavy metals by improving the characteristics of zeolite, which has excellent reactivity toward cationic heavy metals but low reactivity toward pollutants existing as oxyacid anions such as trivalent arsenic and pentavalent arsenic.
[0072] In addition, by manufacturing heavy metal stabilizers in the form of beads, unlike conventional powder materials, there is no risk of loss, and it is possible to prevent contamination of the surrounding ecosystem and groundwater caused by toxic substances leaching from sediments after marine or landfilling of contaminated sediments.
[0073] Furthermore, the zeolite heavy metal stabilizer of the present invention is made by recycling bottom materials that were conventionally landfilled as industrial waste, and thus has excellent effects in terms of securing economic viability through resource recycling and preventing environmental pollution.
[0075] Example 1
[0076] Bottom ash collected from the ash disposal site of Korea Western Power was washed with a 0.1 M HCl solution for 1 hour, and then dried at 105 ℃ for 2 hours to complete the washing and drying process. Next, sodium hydroxide (NaOH) was mixed with the bottom ash from which impurities had been removed in a ratio of 1:1.5 parts by weight, and the mixture was melted using an ignition device at 550 ℃ for 1 hour to selectively extract Si and Al components. Next, 10 parts by weight of distilled water and 0.3 parts by weight of sodium aluminate (NaAlO2) were added per 1 part by weight of the molten product, mixed, and stirred for 6 hours to form an aluminosilicate gel.
[0078] Next, the formed aluminosilicate gel was placed in a hydrothermal synthesis reactor (teflon-lined autoclave) and hydrothermally synthesized at 100 °C for 6 hours to produce bottom ash-based Na-A zeolite (see Fig. 2). XRD analysis was performed on the produced bottom ash-based Na-A zeolite, and it was confirmed that while the bottom ash prior to zeolite synthesis exhibited crystallinity consisting mostly of quartz or mullite, the produced product possessed the crystallinity of Na-A zeolite (see Fig. 3).
[0080] Next, the above-mentioned flooring-based Na-A zeolite is prepared by dissolving iron(III) chloride (FeCl3) in distilled water to obtain 0.1 M trivalent iron (Fe 3+ The solution was added to the reactor at a weight ratio of 1:10, the reactor temperature was raised to 80°C, and the mixture was stirred at 200 rpm for 24 hours to [prepare] Na on the surface of the bottom-material-based Na-A zeolite. + The ion is Fe 3+ It was allowed to undergo ion exchange with ions. After the above ion exchange reaction, the mixture was filtered, and then distilled water was used to remove unreacted trivalent iron (Fe₃) from the surface. 3+) ions were removed and the pH of the washing water was adjusted to 6 to 7. Next, the bottom material-based Fe-A zeolite was prepared by drying at 105°C for 2 hours (see Figures 4 to 5).
[0082] Next, the above-prepared Fe-A zeolite, bentonite, and water were mixed in proportions of 46.8 wt%, 15.6 wt%, and 37.5 wt%, respectively. The mixture was then fed into a ball-making and extrusion device to form beads ranging from 2 to 3 mm, dried at 120°C for 2 hours, and calcined at 650°C for 5 hours to finally produce a floor-material-based zeolite heavy metal stabilizer supported with iron oxide in the form of beads (see Fig. 6). XRD analysis was performed on this, and a peak pattern indicating the crystallinity of γ-Fe2O3, an iron oxide, was observed (see Fig. 7). Meanwhile, a photograph of the actual prepared floor-material-based zeolite heavy metal stabilizer supported with iron oxide in the form of beads is shown in Fig. 8.
[0084] [Experiment 1: Evaluation of Heavy Metal Adsorption Capacity of Bottom Material-Based Fe-A Zeolite Beads in Sediments]
[0085] A bead-shaped iron oxide-supported bottom material-based zeolite heavy metal stabilizer obtained through the process of Example 1 was prepared, and sediment collected from the downstream of Singil Stream passing through the Sihwa-Banwol Industrial Complex was prepared (see Fig. 9). A sediment culture experiment was performed to measure the heavy metal content in the sediment, and the results of measuring the heavy metal content in the sediment are as shown in Fig. 10. Specifically, the heavy metals in the sediment samples were analyzed according to the Water Quality Pollution Process Test Method, and the results showed that arsenic was Grade II, lead and zinc were Grade III, and copper and nickel were Grade IV according to the pollution assessment criteria for river sediment items, confirming contamination by arsenic and heavy metals.
[0086] Next, a bead-shaped iron oxide-supported bottom-material-based zeolite heavy metal stabilizer according to Example 1 was applied to the contaminated sediment sample in amounts of 2 parts by weight, 5 parts by weight, and 7 parts by weight, respectively, based on 100 parts by weight of the contaminated sediment sample, and distilled water was injected to achieve a moisture content of 25% (see Fig. 11).
[0087] The stabilized sediment was placed in a sealed container to simulate a landfill environment and cultured under dark conditions for 4 weeks. Subsequently, samples were collected and a toxicity characteristic leaching procedure (TCLP) test was conducted to confirm the mobility of contaminants. The results of the experiment are shown in Figure 12.
[0088] Figure 12 shows the results of a TCLP test conducted to investigate the mobility of arsenic and heavy metals in contaminated sediments before and after stabilization treatment using a bead-shaped iron oxide-supported bottom-material-based zeolite heavy metal stabilizer. According to the results of Figure 12, the concentrations of arsenic and heavy metals in the TCLP leachate of the sediments before and after stabilization treatment decreased as the application ratio of the stabilizer increased, and it was confirmed that the concentrations of arsenic and heavy metals were reduced simultaneously. Through this, it was confirmed that the bead-shaped iron oxide-supported bottom-material-based zeolite heavy metal stabilizer according to the present invention possesses a risk reduction effect through the stabilization of arsenic and heavy metal-contaminated sediments and enables the simultaneous stabilization of arsenic and heavy metals.
[0089] Meanwhile, interpreting the results, it is determined that the zeolite heavy metal stabilizer based on the iron oxide-supported substrate having a bead form according to the present invention can stabilize arsenic through chemical adsorption by iron oxide on the surface and an iron-arsenic co-precipitation mechanism, and stabilize cationic heavy metals through the cation exchange capacity and alkali precipitation mechanism of the zeolite (see Fig. 13).
[0091] Although specific embodiments of the present invention have been described and illustrated above, it is obvious to those skilled in the art that the present invention is not limited to the described embodiments and can be modified and varied in various ways without departing from the spirit and scope of the present invention. Accordingly, such modifications or variations should not be understood individually from the technical spirit or perspective of the present invention, and the modified embodiments should be considered to fall within the scope of the claims of the present invention.
Claims
Claim 1 a) a step of preparing Na-A zeolite from bottom ash; b-1) 0.01 to 0.1 M trivalent iron (Fe) per 1 part by weight of Na-A zeolite 3+ ) Mix 10 to 100 parts by weight of the solution and stir for 1 to 48 hours at a temperature in the range of 70 to 90 ℃, so that Na in the Na-A zeolite + Ions and Fe in trivalent iron solution 3+ A method for manufacturing a heavy metal stabilizer comprising: a step of inducing ion exchange between ions; b-2) filtering and washing the mixture in which the ion exchange is completed, and drying it at a temperature in the range of 100 to 110 ℃ for 1 to 4 hours to prepare an Fe-A zeolite in which iron ions are supported on the Na-A zeolite; and c) mixing an inorganic binder and water with the Fe-A zeolite and calcining it to produce Fe-A zeolite beads; wherein the heavy metal stabilizer simultaneously stabilizes one or more cationic heavy metals selected from cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), or nickel (Ni) heavy metals and trivalent and pentavalent arsenic anions with respect to a complex contaminated sediment contaminated by cationic heavy metals and arsenic. Claim 2 A method for manufacturing a heavy metal stabilizer according to claim 1, wherein step a comprises washing and drying the flooring material with distilled water and a 0.1 M nitric acid solution (a-1). Claim 3 A method for manufacturing a heavy metal stabilizer according to claim 2, wherein step a comprises mixing a dried flooring material with sodium hydroxide (NaOH) in a weight ratio of 1:1 to 2 parts and melting treatment in a temperature range of 500 to 600 ℃ to leach silicon (Si) and aluminum (Al) from the flooring material (a-2). Claim 4 A method for manufacturing a heavy metal stabilizer according to claim 3, wherein step a comprises mixing the molten product with water to produce an aluminosilicate gel and mixing sodium aluminate (NaAlO2) to adjust the molar ratio of silicon (Si) and aluminum (Al) (a-3). Claim 5 A method for manufacturing a heavy metal stabilizer according to claim 4, wherein step a comprises a step of forming a Na-A zeolite by hydrothermally reacting the aluminosilicate gel at a temperature range of 90 to 110 ℃ for 4 to 8 hours (a-4). Claim 6 delete Claim 7 delete Claim 8 A method for manufacturing a heavy metal stabilizer according to claim 1, wherein step c comprises the step of preparing a mixture of Fe-A zeolite, bentonite, and water into beads and drying at a temperature in the range of 100 to 140 ℃ for 1 to 3 hours. Claim 9 A method for manufacturing a heavy metal stabilizer according to claim 8, wherein step c comprises the step of manufacturing flooring-based Fe-A zeolite beads by calcining the dried beads at a temperature in the range of 600 to 700 ℃ for 1 to 10 hours (c-2). Claim 10 A heavy metal stabilizer manufactured by the method of claim 1, wherein a bottom material-based zeolite supported with iron oxide (γ-Fe2O3) has a bead shape, said stabilizer simultaneously stabilizes a complex contaminated sediment of said cationic heavy metal and arsenic anion by means of cation exchange for one or more cationic heavy metals selected from cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), or nickel (Ni), and by means of chemical adsorption by iron oxide and an iron-arsenic co-precipitation mechanism for arsenic anions selected from trivalent arsenic, pentavalent arsenic, and combinations thereof. Claim 11 In claim 10, the stabilizer has a diameter in the range of 1 to 5 mm, and a BET specific surface area of 50 to 200 m² 2 / g Phosphorus, heavy metal stabilizer. Claim 12 In claim 10, the stabilizer is a heavy metal stabilizer having a stabilization efficiency of 1 to 99% for arsenic (As) contained in the dredged soil sediment, based on the TCLP (toxicity characteristics leaching product) leaching test results according to the particle size, concentration, and application ratio of the sediment. Claim 13 In claim 10, the stabilizer is a heavy metal stabilizer having a stabilization performance of 1 to 99% for cadmium (Cd), copper (Cu), lead (Pb), zinc (Zn), or nickel (Ni) heavy metals contained in the dredged soil sediment, based on the TCLP (toxicity characteristics leaching product) leaching test results according to the particle size, concentration, and application ratio of the sediment. Claim 14 A method for stabilizing heavy metal contaminated sediment, comprising: a step of adding and mixing a heavy metal stabilizer according to claim 10 to a sediment contaminated with arsenic and cationic heavy metals; and a step of adjusting the moisture content of the arsenic and cationic heavy metal contaminated sediment to 10 to 30%. Claim 15 A method for stabilizing heavy metal contaminated sediment according to claim 14, wherein 1 to 10 parts by weight of the heavy metal stabilizer are added based on 100 parts by weight of the arsenic and cationic heavy metal contaminated sediment when the stabilizer is added.
Citation Information
Patent Citations
omitted
KR101241377B1
Method for Manufacturing Synthetic Zeolites using Coal Bottom Ash of thermoelectric power plant
KR101602933B1
Treatment process including selective mercury removal for desulfurization waste water of flue gas
KR101818492B1
method for mass synthesis of Na-A type zeolite using coal fly ash
KR102060505B1
Modified zeolite manufacturing system
KR1020210039048A